The security study of Windows operating system - Ning, Wang. (2013)
Computer architecture and Internet technology develop increasingly fast nowadays. Meanwhile the study of system and net security is playing a more and more important role in preventing Internet security breach and data leakage. Computer scientists should always bear in mind the importance of studying and enhancing computer security system. In this report, the author presented his research on the security feature of Windows operating system through the development of a remote mouse manipulation system in C++. The author explained his design and detailed implementation of this system and further analyzed the test outcomes. Finally conclusion and constructive recommendations for future developers are raised by the author.